Loss of Endothelial Glycocalyx During Normothermic Machine Perfusion of Porcine Kidneys Irrespective of Pressure and Hematocrit - Tobias M. Huijink, MD; Cor J. van ‘t Hof, BSc; L. Annick van Furth, BSc; Nora A. de Haan, BAS; Hanno Maassen, MD; Leonie H. Venema, PhD; Rosa G.M. Lammerts, MD, PhD; Marius C. van den Heuvel, MD; Jan-Luuk Hillebrands, PhD; Jacob van den Born, PhD; Stefan P. Berger, MD, PhD; Henri G.D. Leuvenink, PhD (Transplantation Direct, 2023)
Background. Normothermic machine perfusion (NMP) is a promising modality for marginal donor kidneys. However, little is known about the effects of NMP on causing endothelial glycocalyx (eGC) injury. This study aims to evaluate the effects of NMP on eGC injury in marginal donor kidneys and whether this is affected by perfusion pressures and hematocrits. Methods. Porcine slaughterhouse kidneys (n = 6/group) underwent 35 min of warm ischemia. Thereafter, the kidneys were preserved with oxygenated hypothermic machine perfusion for 3 h. Subsequently, 4 h of NMP was applied using pressure-controlled perfusion with an autologous blood-based solution containing either 12%, 24%, or 36% hematocrit. Pressures of 55, 75, and 95 mm Hg were applied in the 24% group. Perfusate, urine, and biopsy samples were collected to determine both injury and functional parameters. Results. During NMP, hyaluronan levels in the perfusate increased significantly (P < 0.0001). In addition, the positivity of glyco-stained glycocalyx decreased significantly over time, both in the glomeruli (P = 0.024) and peritubular capillaries (P = 0.003). The number of endothelial cells did not change during NMP (P = 0.157), whereas glomerular endothelial expression of vascular endothelial growth factor receptor-2 decreased significantly (P < 0.001). Microthrombi formation was significantly increased after NMP. The use of different pressures and hematocrits did not affect functional parameters during perfusion. Conclusions. NMP is accompanied with eGC and vascular endothelial growth factor receptor-2 loss, without significant loss of endothelial cells. eGC loss was not affected by the different pressures and hematocrits used. It remains unclear whether endothelial injury during NMP has harmful consequences for the transplanted kidney.